Bilateral hind limb amputation and partial cystectomy due to aortic thromboembolism in cat: Case report - Guedes, Stephanya Fagundes; Martins, Fernando Dedding; Cardoso Franco, Glória; Oliva, Karen Soler de Oliveira; Coleto, Arlinda Flores (Pubvet, 2023)
Feline aortic thromboembolism (FATE) is an uncommon condition characterized by the formation of clots in the aorta. Diagnosis is based on clinical signs such as pain, paralysis, absence of a pulse, cyanosis and cooling of the limbs. The etiology is often associated with hypertrophic cardiomyopathy. Treatment is controversial and depends on several factors. Surgical intervention is an option and the AAFP Feline Anesthesia Guidelines are helpful in this context. The prognosis varies and is often reserved, with low survival rates in severe cases. The study describes a clinical case of a young feline, without pre-existing heart disease, who developed FATE. He underwent multiple surgical procedures (thromboembolectomy, partial cystectomy and bilateral amputation of the hind limbs) and had a remarkable recovery, despite low survival expectations according to the literature. The patient remained in good health and quality of life, even 55 days after the last surgery. This suggests that, in selected cases, surgical intervention may be beneficial for the recovery of felines with FATE that have developed irreversible limb ischemia.
Keywords: Aortic trifurcation; cat; thrombus